A review over biodegradable single-use cup based on zeolite composition - Kamberov Konstantin; Ivanova Maria; Stipchekova Martina (E3S Web of Conferences)
The study aims to review the possibility of using zeolite composition for biodegradable beverage cup. It starts with an analysis of existing solutions for food packaging by qualifying each used technologies. Zeolite is further examined, as an alternative, by outlining some specifics especially as a material with good biodegradation and certain technological advantages for its production. Zeolite and its possible binders (casein, gelatine, polyvinyl alcohol and polylactic acid (PLA) are examined in detail, finishing with a focus set on the PLA as suitable binder. Production methods and technologies of zeolite and PLA are examined too, emphasizing their strengths and weaknesses. A comprehensive study of existing technologies and studies is carried out, and a novel composition of zeolite and PLA is proposed for eco-friendly hot beverage packaging. Presented research analysis and review set a good basis for further development of product, based on zeolite and PLA composition.